Educational techniques for teaching and learning business vocabulary - Sorokina, А. (Право и экономика, 2020)
The paper is devoted to educational techniques in teaching and learning business vocabulary. Vocabulary is vital for learners, especially for those who learn English for specific purposes or expect to operate at an advanced level in English.It is useful for both teachers and learners to become aware of the points that will be discussed in this paper.